Analysis of Contractual Structures in Conventional and Sharia Insurance - Sasti Amar Sabila; Jamal Abdul Aziz; Sochimin Sochimin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the contract construction of conventional insurance and sharia insurance, focusing on differences in legal relationships, risk management mechanisms, fund ownership status, claim payment sources, supervision, and participant protection. This research uses a qualitative approach with a descriptive-comparative design. Data were collected through literature study and document analysis, including laws and regulations, DSN-MUI fatwas, academic books, journal articles, and relevant case studies related to conventional and sharia insurance practices. The data were analyzed using content analysis by classifying the findings into several themes, namely contract structure, risk distribution, fund management, claim mechanisms, investment management, and supervision. The results show that conventional insurance is based on the principle of transfer of risk, in which participants transfer risk to the insurance company through premium payments. In contrast, sharia insurance applies the principle of sharing of risk through tabarru’ funds, where participants collectively assist one another when a covered risk occurs. The study also finds that conventional insurance positions the company as the owner of premiums and risk bearer, while sharia insurance positions the company as a fund manager based on contracts such as tabarru’, wakalah bil ujrah, and mudharabah musytarakah. This study contributes to strengthening the understanding that contract construction is a substantive element that determines legitimacy, fairness, transparency, and participant protection in insurance practices.